2002
DOI: 10.1017/s0021859601001708
|View full text |Cite
|
Sign up to set email alerts
|

Wet–cold preservation of West African yam (Dioscorea spp.) pollen

Abstract: Hermetic cold storage without previous drying (wet-cold storage) was experimented for the preservation of yam pollen grains. Pollens collected from white yam D. rotundata and a wild relative, D. praehensilis, were stored at k80, k20, 5, and 15 mC in sealed packs for 2 years. Pollen samples were drawn for in vitro germination tests after 100 and 700 days, and hand pollination was conducted after 365 and 730 days in storage. Pollen germination responses were not significantly different among the two species. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 0 publications
1
20
2
Order By: Relevance
“…Based on this study, the collected pollen should be used within 2 h for maximum results, as the viability is significantly reduced after 3-4 h. The screening of a large number of genotypes will be challenging as it takes 8-12 min for culturing pollen in a single Petri dish. Moreover, the recommended time for yam pollen collection is limited to the morning hours (8-11 a.m.) [8]. Rapid viability testing methods will, therefore, be necessary if high throughput phenotyping is desired for yam pollen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study, the collected pollen should be used within 2 h for maximum results, as the viability is significantly reduced after 3-4 h. The screening of a large number of genotypes will be challenging as it takes 8-12 min for culturing pollen in a single Petri dish. Moreover, the recommended time for yam pollen collection is limited to the morning hours (8-11 a.m.) [8]. Rapid viability testing methods will, therefore, be necessary if high throughput phenotyping is desired for yam pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Yam hybridization activities are often constrained by low, irregular and asynchronous flowering [5,6]. Selecting suitable pollen parents and preserving yam pollen for future use are potential means of managing these constraints [6,8]. However, implementing these practices in yam breeding programs requires a cost-effective and reliable pollen viability testing protocol, allowing the discrimination of genotypes for viability status and efficient monitoring of stored pollen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daniel et al (2002) have described conditions for preservation of yam pollen. The cold storage of pollen without pre-drying at -20 or -80 • C for periods as long as 2 years or more is an efficient means of conservation.…”
Section: Breeding Methods and Techniquesmentioning
confidence: 99%
“…and Daniel et al (2002) concluded that the maintenance of pollen grains of yam would be better at high moisture levels, arguing that the potential fertility of pollen grains is highest at shedding and at this stage, yam pollen grains are sticky (Ngu, 1991), indicating a high moisture content. This paper examines potential protocols for sustainable pollen storage based on results from various experiments conducted on the pollen grains of different West African yam genotypes.…”
Section: Introductionmentioning
confidence: 99%